Commitment in same-sex love relationships - Lewis, Robert A.; Kozac, Ellen B.; Milardo, Robert M. (Homosexuality and psychology, psychiatry and counseling)
"Robert A. Lewis; Ellen B. Kozac; Robert M. Milardo; et al.... Fonds Suzan Daniel (FSD)"